A new species of Aclees from Taiwan with notes on other species of the genus (Coleoptera: Curculionidae: Molytinae) - Meregalli, Massimo; Boriani, Marco; Taddei, Andrea; Hsu, Chen-Fu; Tseng, Wei-Zhe; Mouttet, Raphaëlle (Zootaxa, 2020)
A molecular and morphological analysis of the species of Aclees native to Taiwan allowed for recognition of a new species, that is described here as Aclees aenigmaticus Meregalli & Boriani, sp. n. The study also revealed that the species of Aclees that has been introduced into Italy and France has identical morphology and mitochondrial cox-1 gene sequence with specimens of A. taiwanensis from Taiwan. Taiwan is thus assumed to be the country of origin of the specimens introduced into Europe. A key to the species of Aclees present in Taiwan is provided. A lectotype is designated for Aclees foveatus Voss, 1932, and some remarks on A. hirayamai Kôno, 1932 are given. Pagiophloeus visayus Heller, 1929 from the Philippines is transferred to the genus Aclees, comb. n.